(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
This article presents on some perspectives on reading. It considers reading as a robust resource and skill for learning. Reading is one of the major avenues of communication. It has occupied a good space at the Nepalese educational system. This is a review article where an in-depth information and insight has been reviewed. The techniques that are used in this study are document review and theoretical knowledge. Relevant literature is reviewed to make the study conceptually and theoretically reliable and authentic. The study shows that to read is to lead. The desire to write comes from reading. It demands both passion and compassion to be a voracious reader. It is not only receptive but an active, communicative and interactive skill. It leads to understanding, communication, capacity building, critical thinking, testing and assessment. It is the means by which every age is linked to every other. It makes possible reader’s capacity for time binding, the ability to perceive himself or herself in the historic process and the fluid universe around him or her. Teaching reading is a humanizing process. Reading involves skills and thinking. It affects the entire personality. Through reading the learner can view ever-widening horizons and explore ever-new areas in the world of things, people and events. The key to learning, therefore, is the cultivation not only of the ability to read, but also of the love of reading.